دور الصناعات التحويلية في النمو الاقتصادي في سورية (2000-2020) دراسة عملية باستخدام فرضيات كالدور في النمو (مجلة جامعة دمشق للعلوم الاقتصادية و السياسية, 2026)
The research presents a statistical analytical study to test Kaldor's law with its three hypotheses about the role of the manufacturing industry in the growth of the Syrian economy. It explains the role of industry in the growth of the Syrian GDP and its relationship to increasing productivity and with other economic sectors. The research concluded that the manufacturing industry sector needs three years to achieve a balanced relationship with regard to its contribution to the growth of the GDP, and in parallel it needs three years to reach a positive balanced relationship between the productivity of the worker in the industrial sector and the growth of the industrial sector. However, it needs about 5 years to reach a positive balanced relationship with other economic sectors contributing to the growth of the GDP in Syria.
Keywords: قانون كالدور للنمو; الصناعات التحويلية; اختبار ديكي فولر الموسع; اختبار جوهانسن; نمو الناتج الاجمالي المحلي